2015
DOI: 10.1016/j.freeradbiomed.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of serum lipid profile, SRB1 loss, and impaired Nrf2 activation in CDKL5 disorder

Abstract: CDKL5 mutation is associated with an atypical Rett syndrome (RTT) variant. Recently, cholesterol homeostasis perturbation and oxidative-mediated loss of the high-density lipoprotein receptor SRB1 in typical RTT have been suggested. Here, we demonstrate an altered lipid serum profile also in CDKL5 patients with decreased levels of SRB1 and impaired activation of the defensive system Nrf2. In addition, CDKL5 fibroblasts showed an increase in 4-hydroxy-2-nonenal– and nitrotyrosine–SRB1 adducts that lead to its ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…We did however find that metformin stimulates the PGC-1α/Nrf2/HO-1 signaling pathway selectively in RTT mouse brain. Indeed, previous works suggested that alterations in the activation of Nrf2 may be responsible for the increased oxidative stress in RTT [59]. In fact, the stimulation of PGC-1α/Nrf2 pathway is known to boost the expression of fundamental mitochondrial antioxidant genes, preventing oxidative injury and mitochondrial dysfunction [60].…”
Section: Discussionmentioning
confidence: 99%
“…We did however find that metformin stimulates the PGC-1α/Nrf2/HO-1 signaling pathway selectively in RTT mouse brain. Indeed, previous works suggested that alterations in the activation of Nrf2 may be responsible for the increased oxidative stress in RTT [59]. In fact, the stimulation of PGC-1α/Nrf2 pathway is known to boost the expression of fundamental mitochondrial antioxidant genes, preventing oxidative injury and mitochondrial dysfunction [60].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the pathophysiological role of HNE have continued in a collaboration with Giuseppe Valacchi [92,93]. We first met on the tennis courts of the University of California at Davis when Giuseppe was a postdoc in Carroll Cross’s laboratory.…”
Section: Mechanisms Of Signaling By Electrophilesmentioning
confidence: 99%
“…Several lines of evidence also implicate aberrant mitochondrial function in CDD. Notably, the oxidative stress marker 4HNE-PAs (9) are also present in CDD patient serum, and one study showed that CDKL5-deficient fibroblasts exhibited reduced levels of NFE2L2, an apparent protective mechanism against oxidative stress (12). Additionally, studies in a Cdkl5null mouse model of CDD identified brain mitochondrial functional abnormalities (13).…”
Section: Introductionmentioning
confidence: 99%